Tanshinone IIA protects against lipopolysaccharide‐induced lung injury through targeting Sirt1. (13th March 2019) - Quan, Minxue; Lv, Yanni; Dai, Yang; Qi, Biying; Fu, Longsheng; Chen, Xuanying; Qian, Yisong
Abstract: Objectives: This study was designed to investigate the effects and the mechanism of Tanshinone IIA (TIIA) on endotoxic shock‐induced lung injury in a mouse model. Methods: Mice were administered intraperitoneally with TIIA (10 mg/kg) 0.5 h before lipopolysaccharide (LPS) challenge and then received additional injections every 24 h during the 3‐day experimental period. The physiological indexes, the survival rate and the parameters for lung injury were examined. The protein levels of Sirt1, and the acetylation and activation of NF‐κB p65 were determined. The expression and secretion of pro‐inflammatory factors were evaluated, respectively. Key findings: Treatment with TIIA significantly improved physiological indexes and increased the survival rate of mice in response to LPS challenge. TIIA treatment displayed an obvious up‐regulation of Sirt1 protein, in accompany with reduced acetylation and activation of NF‐κB p65 following LPS stimulation. In addition, TIIA attenuated LPS‐induced lung injury and prevented the expression and secretion of pro‐inflammatory factors. However, the protective effects of TIIA were abolished by Sirt1 inhibitor. Conclusions: Tanshinone IIA prevents LPS‐induced secretion of pro‐inflammatory cytokines thus exerts protective effects against acute lung injury, probably via modulation of Sirt1/NF‐κB signalling pathway.